Use of Tripolyphosphate in the Development of Products from Minced Meat - Basu, Subrata (Fishery Technology, 2025)
Sodium tripolyphosphate can be used with several advantages in dried products prepared from minced fish. It lowers the water activity (aw) of the product and has got bactericidal property. It increases hydration of the protein and increases resistance o thermal denaturation of the protein.